Pengembangan Multimedia Interaktif Berbasis Articulate Storyline 3 Materi Gaya untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDN Gayam 2 - Juneta Amelia Putri; Muhamad Basori; Erwin Putera Permana (Mataram University, 2026)
Learning science and social studies (IPAS) in elementary school requires media that can present material in a concrete, engaging, and interactive way so that students can more easily understand the concepts being taught. However, learning IPAS in the 4th grade at SDN Gayam 2 is still dominated by lectures and textbook use, making it difficult for students to understand the material on the effects of force on objects. This study aims to develop interactive multimedia based on Articulate Storyline 3 that is valid, practical, and effective for the material on the effects of force on objects. This research uses a Research and Development (R&D) method with the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 23 4th-grade students at SDN Gayam 2, including 8 students in a limited trial and 15 students in a wider trial. Data collection techniques used observation, interviews, questionnaires, and tests. Data analysis was conducted to determine the level of validity, practicality, and effectiveness of the media. The research results show that the developed interactive multimedia achieved a validity of 83%, categorized as very valid, practicality of 92%, categorized as very practical, and effectiveness with an N-Gain value of 0.75, categorized as high. Therefore, interactive multimedia based on Articulate Storyline 3 is suitable to be used to improve student learning outcomes.